Humour in the Situational Comedy Balada Kampung Riwil - Mytha Candria (Endogami: Jurnal Ilmiah Kajian Antropologi, 2023)
Humor is a universal human phenomenon that is culturally bounded. As an instance of expressive culture, humor communicates a set of beliefs and thoughts held by and shared in a community. This is the reason humor has for recent decades attracted the attention of anthropologists. A lot of humors are expressed in verbal language, and in this way linguistics, particularly pragmatics, provides an analytical tool to understand the meanings of humor. Humorous utterances in this study were taken from episode 118, entitled “Dyah Puspa Jaladri#1”, of a Javanese comic serial Balada Kampung Riwil. The data were analyzed using Grice’s Cooperative Principle to reveal the meanings behind the humor. The result shows that amusing effects arise when Grice’s maxims are intentionally flouted and humor in the serial serves various functions.